Derecho de la mujer a no discriminación en razón al sexo: Fuerzas Armadas y Policía Nacional del Perú - Mendoza Rodriguez, Karla Patricia (2019)
ABSTRACT Discrimination, it is accurate, is as old as civilization and this has been built - as some writers mention - on the sacrifice of individuals and discriminated social sectors: slavery. The emergence of the Rule of Law and later of the Constitutional State of Law has allowed, with certain limitations, a more orderly struggle to face discrimination, which generally falls on women, ethnic groups, religious minorities, migrants, people with disabilities or with sexual preferences. different from the majorities, who suffer physical, psychological and other violence, from discriminatory practices. The struggle for non-discrimination is a vital reality, which requires the efforts of citizens and local, regional, national and international organizations. The research is aimed at presenting a coherent picture and response, from a legal point of view, to the issue of discrimination and above all to discrimination by sex, of women and more specifically, of the female cadet who enters, to integrate the Armed Forces and Police Forces in Peru, presenting a normative protective framework of International - National level; as well as constitutional jurisprudence that has been graphed, the respect that the military and police formative entities must have towards the cadet woman, when she becomes pregnant, during her educational process of professional formation, proposing the validity of the following Fundamental Rights: Of the Family, Of Equality, Non-Discrimination and the Right to Education that women should enjoy, in the performance of their status as citizens, for the full development of their personality.